أثر الابتكار في العمليات على جودة الخدمة المصرفية - قريشي، شيماء; منصوري، رقية (جامعة الوادي University of Eloued, 2025)
هدفت الدراسة إلى معرفة مستوى توفر الابتكار في العمليات بأبعاده المختلفة (الابتكار في تصميم الخدمة، الابتكار في لحظة الصدق، الابتكار في خدمة العملاء) وأيضا مستوى جودة الخدمة المصرفية في المصارف محل الدراسة، وبيان تأثير الابتكار في العمليات على جودة الخدمة المصرفية، واستخدمنا طريقة العينة العشوائية البسيطة في توزيع 90 استبانة على الزبائن في المصارف محل الدراسة في ولاية بسكرة، وتم استرداد 77 استبانة صالحة للتحليل الاحصائي. توصلت الدراسة إلى عدة نتائج أهمها مستوى توفر الابتكار في العمليات جاء متوسطا ومستوى توفر جودة الخدمة المصرفية في المصارف محل الدراسة جاء مرتفعا وفقا لمقاييس الدراسة، لذلك وجد تأثير ذو دلالة إحصائية للابتكار في العمليات بأبعاده المختلفة على جودة الخدمة المصرفية في المصارف محل الدراسة، واقترحت الدراسة ضرورة الاهتمام بالابتكار في عملية تقديم الخدمة لما لها أثر ايجابي على جودة الخدمات المصرفية المقدمة للعملاء. The study aimed to find out the level of availability of innovation in operations in its various dimensions (innovation in service design, innovation in the moment of honesty, innovation in customer service) as well as the level of quality of banking service in the banks under study, and to demonstrate the impact of innovation in operations on the quality of banking service.we used a simple random sample Method to distribute 90 questionnaires to customers in the banks under study in Biskra state, and recovered 77 questionnaires valid for statistical analysis. The study reached several results, the most important of which was the level of availability of innovation in operations came on average and the level of availability of banking service quality in the banks under study came high according to the study standards, so a statistically significant impact of innovation in operations in its various dimensions was found on the quality of banking service in the banks under study, and the study suggested the need to pay attention to innovation in the process of providing service because it has a positive impact on the quality of banking services provided to customers.
The impact of innovation in operations on the quality of banking service a sample study of banks in Biskra
Keywords: ابتكار; تصميم الخدمة; لحظة الصدق; خدمة العملاء; جودة الخدمة المصرفية; innovation; service design; moment of truth; customer service; quality of banking service